1986
DOI: 10.1002/ijc.2910380120
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and characterization of high‐affinity membrane receptors for tumor necrosis factor on human leukemic cell lines

Abstract: The expression of specific membrane receptors for TNF-alpha was determined on various human leukemic cell lines differing in their sensitivity to the growth-inhibitory activity of TNF-alpha. Binding studies with 125I-labelled TNF-alpha indicated specific binding in 8/10 cell lines with approximately 10-fold differences in the quantity of TNF-alpha bound by these distinct cell lines. Scatchard analyses of TNF-binding revealed the existence of high-affinity membrane receptors (Kd 1.5 X 10(-10) M) and approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
47
0
2

Year Published

1987
1987
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 21 publications
2
47
0
2
Order By: Relevance
“…Cross-linking of 125I-lymphotoxin to its receptor and immunoprecipitation with the use of anti-TNF-a Inh would answer the question of whether the inhibitor also recognizes the 120-kDa structure. Alternatively, T cells represent a heterogeneous population, and it cannot be excluded that this represents TNF receptor expression of cellular subpopulations as its heterogeneity in regard to the molecular mass has been reported by several groups (31)(32)(33). This is less likely, however, because FITC-coupled TNF-a should bind its own receptor independently of the cellular subpopulation.…”
Section: Discussionmentioning
confidence: 98%
“…Cross-linking of 125I-lymphotoxin to its receptor and immunoprecipitation with the use of anti-TNF-a Inh would answer the question of whether the inhibitor also recognizes the 120-kDa structure. Alternatively, T cells represent a heterogeneous population, and it cannot be excluded that this represents TNF receptor expression of cellular subpopulations as its heterogeneity in regard to the molecular mass has been reported by several groups (31)(32)(33). This is less likely, however, because FITC-coupled TNF-a should bind its own receptor independently of the cellular subpopulation.…”
Section: Discussionmentioning
confidence: 98%
“…Both TNF-Rs have been objects of intense physiological and biochemical investigations. Likewise, the ligand binding properties of the TNF-Rs have been extensively studied (8)(9)(10)(11) although a detailed analysis became feasible only after the molecular cloning of the two individual receptor molecules. Equilibrium binding studies with 125 Ilabeled TNF ( 125 I-TNF) at 0°C defined high-affinity binding of TNF to both TNF-Rs with K d values of approximately 300-600 pM for TNF-R1 and 70-200 pM for TNF-R2 (12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Several investigators have identified TNF receptors at the surface of a variety of cell types. A single class of high-affinity sites with Kd in the range of 0.1-1.0 nM and a few hundred to a few thousand copies per cell has been reported (13)(14)(15). The approximate molecular size of the TNF-a-binding proteins, as determined in crosslinking studies, varies from '50 kDa to 140 kDa (15,16 …”
mentioning
confidence: 99%
“…4). Raji cells have no detectable TNF-binding sites (15) and were used to assess the nonspecific binding of the reagents. With HEp-2 cells a positive immunofluorescence was found only with mAb htr-9 and was not found with (Fig.…”
mentioning
confidence: 99%